Cultural Influences in Poet Nazar Qabbani's Experience: A Case Study of "My Story with Poetry" - alja'afreh , Khldoon ahmad abdel mon'em (Journal of Ecohumanism, 2024)
Objectives: The study aims to identify the cultural influences and sources in the poetic experience of Nizar Qabbani as described in his book قصتي مع الشعر "My Story with Poetry". It also discusses these influences and their mechanisms in his poetic texts especially that Qabbani's book serves as a key reference for understanding the nature, depth, and significance of the poet's journey. Methodology: The study employed the descriptive analytical approach for its ability to identify and discuss the sources and influences, as well as explain the mechanism of their influence in the poetic text. Results: The study reached several conclusions, the most important of them are: Qabbani's childhood, family, and where he lived had a significant effect on the themes, language, and thoughts of his poetry. Moreover, Qabbani's engagement with the Arab and Western cultural and artistic influences was evident, reflecting in his poetic texts through language, styles, and perspective. The study also showed that Qabbani has contradictory views on the issues of women and love. Previous Studies: The researcher did not find any study that discussed the cultural influences of Qabbani's poetry, which gives the study its artistic and critical value. Conclusion: "My Story with Poetry" has both cultural and critical value in knowing the ins and outs of Qabbani's poetic journey, cultural sources, critical beliefs, and poem-writing process.